2012
DOI: 10.1038/ng.1106
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in axonemal dynein assembly factor DNAAF3 cause primary ciliary dyskinesia

Abstract: Primary Ciliary Dyskinesia (PCD) most often arises from loss of the dynein motors that power ciliary beating. Here we show that PF22/DNAAF3, a previously uncharacterized protein, is essential for the preassembly of dyneins into complexes prior to their transport into cilia. We identified loss-of-function mutations in the human DNAAF3 gene in patients from families with situs inversus and defects in assembly of inner and outer dynein arms. Zebrafish dnaaf3 knockdown likewise disrupts dynein arm assembly and cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
237
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(265 citation statements)
references
References 68 publications
8
237
3
1
Order By: Relevance
“…Dysfunction in dynein heavy chain families is asso- ciated with primary ciliary dyskinesia, 26 which presents with respiratory infection, situs inversus, and sometimes hydrocephalus. Cases of primary ciliary dyskinesia-associated hydrocephalus in humans have previously been reported, although the causative mutations have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction in dynein heavy chain families is asso- ciated with primary ciliary dyskinesia, 26 which presents with respiratory infection, situs inversus, and sometimes hydrocephalus. Cases of primary ciliary dyskinesia-associated hydrocephalus in humans have previously been reported, although the causative mutations have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in dynein assembly factor, DNAAF3, induce primary cilia dyskinesia and disturbance of left-right asymmetry in mice. 38 In embryos with mutations of Noto, a transcription factor regulating cilia formation, left-right asymmetry of internal organs and expression of laterality markers is randomized. 39 The Notch ligand Dll1- …”
Section: Node Cell Monocilia Create Leftward "Nodal Flow" and Activatmentioning
confidence: 99%
“…All of these assembly factors function together in the assembly of ODAs, but are considered to have distinct roles in the process. In conjunction with studies in Chlamydomonas, DNAAF1/ODA7, DNAAF2/PF13, and DNAAF3/PF22 have been shown to function as a chaperone complex for proper folding of the dynein-HCs [128]. DYX1C1 (also named DNAAF4) is also an assembly factor for dynein.…”
Section: Cytoplasmic Assembly Of Axonemal Componentsmentioning
confidence: 84%